Pengaruh Intellectual Capital, Good Corporate Governance, dan Corporate Social Responsibility terhadap Kinerja Keuangan dengan Ukuran Perusahaan sebagai Moderasi: Studi Empiris pada Perusahaan Perbankan yang tercatat di BEI periode 2019-2023 - Dila Nur Aisyah; Andy Dwi Bayu Bawono (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Financial performance serves as a key indicator for assessing a company's overall health, the effectiveness of asset management, and its ability to increase revenue and generate profits. Evaluating financial performance is crucial for understanding the extent to which a company can achieve its financial objectives. This study aims to examine the influence of Intellectual Capital, Good Corporate Governance, and Corporate Social Responsibility on financial performance, with firm size acting as a moderating variable. The research sample consists of banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023, with 31 companies observed each year. The sample was selected using a purposive sampling technique, resulting in 137 observations based on predetermined criteria. The analysis method employed in this study is descriptive statistical analysis with a quantitative approach. Research data were obtained from official reports available on the Indonesia Stock Exchange website, and data processing was carried out using SPSS version 25. The findings reveal that Intellectual Capital does not have a significant effect on financial performance. In contrast, Good Corporate Governance and Corporate Social Responsibility both show a positive influence on financial performance. Meanwhile, firm size does not moderate the relationship between Intellectual Capital, Good Corporate Governance, or Corporate Social Responsibility and financial performance.